External debt vulnerability in emerging markets and developing economies during the COVID-19 shock. Issue 1 (22nd February 2021) - Elkhishin, Sarah; Mohieldin, Mahmoud
Abstract : Purpose: This paper aims to assess to what extent the COVID-19 shock is expected to create a debt crisis in emerging markets and developing economies (EMDEs) through two main questions: what are the main determinants of EMDEs external vulnerability? How vulnerable are EMDEs to the current COVID-19 shock compared to the global financial crisis (GFC)? Design/methodology/approach: In addition to a descriptive analysis of the determinants of EMDEs external vulnerability, this paper designs two sub-indices of overindebtedness and financial fragility that capture EMDEs' distinct characteristics. The two sub-indices together illustrate the overall external vulnerability to the current shock. Findings: EMDEs are more vulnerable compared to the GFC era. Current debt threats arise mainly from debt architecture and the domination of volatile debt forms – primarily foreign currency-denominated bonds. Excessive fear of debt-deflation spirals after the GFC prompted EMDEs to expand their growth trajectories through a pattern of cheap private lending, loose measures and unmonitored fiscal expansion. Research limitations/implications: Conclusive post-crisis data are still unavailable. Practical implications: EMDEs need to balance between temporary accommodative measures and a post-shock policy mix that prevent a deflation spiral without worsening indebtedness and financial fragility. Moreover, financial prudence in face of growing credit demand is crucial, particularly in light of the monetary expansion and injected liquidity. Originality/value: The indices offer a framework for examining external vulnerability in EMDEs based on theoretical and historical revisions, IMF benchmarks and EMDEs specific debt characteristics. The indices components can be offered for empirical examination in separate future research once conclusive data become available.